The Analysis of Pandanus Relationship of Purwodadi Botanical Garden Collections Based on Morphological Character and Molecular Marker (trnL and trnL-F) - Rachma, Risca Adiyani; Hendrian, Hendrian; Azrianingsih, Rodiyati (Research Journal of Life Science, 2017)
The morphological characteristics of plant vegetative organ has the potential to be the defining factor of pandanus family collection at Purwodadi Botanical Garden (PBG). However, the information is not enough to confirm the identity of pandanus at the type-level. This problem happened at the collection of PBG. It is an urgent issue considering PBG as one of the most important ex-situ plant conservation institute that also has function as a study source for plant taxonomy science in Indonesia. Therefore, the use of molecular technology analysis using molecular marker (primer) is incredibly important to identify the member of pandanus family by identifying its family relationship pattern. This information was expected to give a clarity about the identity of Pandanus family at PBG which will support further research and activity for pandanus conservation. The plant sample includes 16 specimens of pandanus with one member of the family from Freycinetia as the outgroup. Morphological analysis of the 50 characteristics of vegetative organs (leaf, stem, and root) was conducted. Molecular analysis of DNA using primer of trnL and trnL-F. The data sequence as a result of the analysis was then tested using homology test with BLAST. All of the DNA sequence was paralleled using Clustal W analysis, the tree construction relationship was analysed using Maximum Parsimony (MP) method with MEGA 6.0 program. The results of morphological studies showed the character vegetative that is the position of the spines on the leaves, the shape of apex leaf and the condition of the root surface above the soil. Molecularly, appears 1 new genera that has not been previously identified by PBG researcher is Benstonea.